Master track of SONNE cruise SO308/1 in 1 sec resolution (zipped, 186 MB) - Achterberg, Eric Pieter (GEOMAR - Helmholtz Centre for Ocean Research Kiel, 2025)
Raw data acquired by position sensors on board RV SONNE during expedition SO308/1 were processed to receive a validated master track which can be used as reference of further expedition data. During SO308/1 the motion reference unit Kongsberg SeaTex AS MRU-5 combined with Kongsberg SeaTex AS Seapath 320 and two GPS receivers SAAB MGL-4 were used as navigation sensors. Data were downloaded from DAVIS SHIP data base (https://dship.bsh.de) with a resolution of 1 sec. Processing and evaluation of the data is outlined in the data processing report. Processed data are provided as a master track with 1 sec resolution derived from the position sensors' data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.
Keywords: 1 sec resolution